Response of microbial diversity and function to the degradation of Barkol Saline Lake - Liu, Yong-Hong; Gao, Lei; Jiang, Hong-Chen; Fang, Bao-Zhu; Huang, Yin; Li, Li; Li, Shuai; Abdugheni, Rashidin; Lian, Wen-Hui; Zhang, Jing-Yi; Yang, Zhen-Dong; Mohamad, Osama Abdalla Abdelshafy; et al. (Frontiers in Microbiology, 2024)
Barkol Lake, a shrinking hypersaline lake situated in the northeast of Xinjiang, China, has experienced the exposure of its riverbed and the gradual drying up of its original sediment due to climate change and human activities, resulting in the formation of alkaline soils. These changes have correspondingly altered the physicochemical characteristics of the surrounding environment.Microorganisms play a crucial role with special functioning involved in various nutrient cycling and energy transfer in saline lake environment. However, little is known about how the microbial community dynamics and metabolic functions in this shrinking saline lake with the degradation process. To address this knowledge gap, a cultivation-independent method of amplicon sequencing was using to identify and analyze the microbial community and its potential ecological functions from the sediment and degraded area. It was found that the microbial community diversity was significantly lower in the degraded areas than that in the sediment samples. The Pseudomonadota was dominant in Barkol saline lake. The abundance of Desulfobacterota and Bacillota in the degraded areas were lower than in the lake sediment, while Pseudomonadota, Acidobacteriota, and Actinobacteriota showed an opposite trend. The βNTI showed that microbial community assembly was primarily associated with deterministic processes in Brakol saline lake ecosystems, and by stochastic processes at the boundary between sediment and degraded areas. Functional predictions showed that sulfur metabolism, particularly sulfate respiration, was much higher in sediment samples than in the degraded areas. Overall, these findings provided a possible perspective for us to understand how microorganisms adapt to extreme environments and their role in saline lakes under environmental change.